Strain-specific differences in cerulein-induced acute and recurrent acute murine pancreatitis - Alexandra Demcsák; Thanh Tran; Miklós Sahin-Tóth; Andrea Geisz-Fremy (Scientific Reports)
Abstract Hyperstimulation with the secretagogue cerulein is a commonly used experimental model to study acute, recurrent acute and chronic pancreatitis in mice. Earlier studies showed that inbred mouse strains had different susceptibility to cerulein-induced pancreatitis. Here, we confirm and extend these findings by characterizing the severity of acute and recurrent acute pancreatitis in the C57BL/6N and FVB/N strains. When acute pancreatitis was induced with repeated cerulein injections, FVB/N mice had more severe pancreatic edema, higher plasma amylase levels, increased inflammatory cell infiltration, and more extensive acinar cell necrosis relative to the C57BL/6N strain. Cerulein elicited higher and more sustained trypsin activity in FVB/N mice relative to C57BL/6N animals, which was likely due to the lower expression of the SPINK1 trypsin inhibitor and the trypsinogen-degrading lysosomal protease cathepsin L. In C57BL/6N mice, we previously showed that pancreatitis responses were more severe during a second attack compared with the initial, sentinel episode. In FVB/N mice, we now found that the second episode was associated with lower pancreas edema and plasma amylase but higher inflammatory cell infiltration than the first attack. The observations reinforce the notion that inbred mouse strains exhibit differences in their pathological responses during acute and recurrent acute pancreatitis.